Regarding the Creativity of the Students of Academic Group - Poškus, Kazys (Acta Paedagogica Vilnensia, 1993)
The article emphasizes that creativity is important for highly qualified representatives of all professions, and especially – teachers. Creativity was lacking in the Soviet school. Therefore, the education of future teachers needs to foster their independence, non-conformity, imagination, the ability to develop creative solutions to educational problems. The survey of Vilnius University students who had a special course to develop creativity in Soviet times revealed that this course was not as effective as expected. Low student activity during the course had various causes: unfavourable study atmosphere, negative attitude towards the profession of the teacher, atrophy of some student features, such as attention, volition, direction, etc., and teaching quality shortcomings of the course. A 1991 survey of the students of the Department of Chemistry, future teachers, found that only few of them have a high degree of creativity, and academic formation of creativity factor is not significant, but creativity is correlated with the popularity of the student within group.
Keywords: creativity; academic group; study quality